Duration of spermatogenesis and identification of spermatogonial stem cell markers in a Neotropical catfish, Jundia (Rhamdia quelen) - Lacerda, S. M. S. N. (2019)
Spermatogenesis is a process driven by stem cell, where germ cell cycle is under the control of a specific genotype species. Considering that Jundia. (Rhamdia quelen) is a Neotropical catfish with great economical importance and useful experimental model, little information is available on basic aspects of its reproductive biology, especially on spermatogenesis. As a result, this study aimed to characterize the male germ cells, estimate the duration of spermatogenesis and evaluate the expression of selected stem cell genes in Jundia testis. Similar to other fish species, our results showed a remarkable decrease of germ cell nuclear volume during Jundia spermatogenesis, particularly from type A undifferentiated to late type B spermatogonia and from diplotene to late spermatids. Using a S-phase marker, bromodeoxyuridine (BrdU), the combined duration of meiotic and spermiogenic phases in this species was estimated in approximately 7 days. This is considered very short when compared to mammals, where spermatogenesis last from 30 to 74 days. Selected stem cell genes were partially sequenced and characterized in Jundia testis. Expression analysis showed higher plzf and pou5f3 mRNA levels in the cell fractions enriched by type A undifferentiated spermatogonia. These results were further confirmed by in situ hybridization that showed strong signal of plzf and pou5f3 mRNA in type A undifferentiated spermatogonia. Altogether, these information will expand our knowledge of the reproductive biology of this species, contributing to improve its production and management, and also for biotechnological applications, such as germ cell transplantation.